Synthesis, Characterization and Chelating Properties of 4-Butyrylsemicarbazone-1-phenyl-3-methyl-2-pyrazolin-5-one - J. D. Patel; P. J. Shah (E-Journal of Chemistry)
4-Butyrylsemicarbazone-1-phenyl-3-methyl-2-pyrazolin-5-one (BUMP-SC) was prepared and its metal chelates of Cu2+, Ni2+, Co2+, Mn2+, Fe2+, Fe3+, Cr3+, UO2 and OV were prepared. The ligands and its chelates were characterized by elemental analysis, metal:ligand (M:L) stoichiometry, IR-electronic spectral studies and magnetic properties. The compounds also were screened for their antimicrobial activity.